Pengembangan Media Pembelajaran Flash Card Audio Visual untuk Meningkatkan Kemampuan Bahasa Ekspresif Anak Gangguan Spektrum Autism (ASD) - Megga Wati; Sukinah Sukinah (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2026)
This study focused on the development of audiovisual flashcard learning media to address language limitations in children with Autism Spectrum Disorder (ASD). The research demonstrated that the created media was valid, practical, and effective in enhancing expressive language skills among children with ASD. This study used the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development research model. The study subjects were two teachers and seven students in Dumai City. The limited trial was conducted by two teachers and two students. The effectiveness test was conducted by five teachers and seven students. The feasibility assessment was conducted by two material experts, one media expert, and two teachers. Data were collected through interviews, observations, questionnaires, and performance assessments. Data analysis used descriptive statistical techniques based on the mean and effectiveness testing using the Wilcoxon test. The results indicate that the audio visual flashcard learning media product produced is a hardware based expressive language learning tool for students with autism. The media is declared feasible in terms of material with an average feasibility score of 4.96 in the very feasible category. The media is declared feasible in terms of practicality test with an average feasibility score of 4.8 in the very feasible category. Audio visual flash card learning media demonstrated significant effectiveness, resulting in a 12.43% increase in learning outcomes.